1987
DOI: 10.1210/endo-120-1-409
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Induced Hypoglycemia Activates the Release of Adrenocorticotropin Predominantly via Central and Propranolol Insensitive Mechanisms

Abstract: The dynamic patterns of pituitary-adrenocortical and sympatho-adrenal hormone responses to insulin hypoglycemia as well as the relative importance of central vs. peripheral control of hypoglycemia-induced ACTH secretion were evaluated. In conscious rats bearing indwelling cannulae, the changes in hormone concentrations after insulin injection were dependent on the changes in blood glucose levels with respect to both time course and magnitude. ACTH, corticosterone, epinephrine, and norepinephrine levels were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…The interassay variation was 10% and intra-assay variation 5.5%, respectively. Concentrations of ACTH were measured in 50 µl of unextracted plasma as described earlier [33]. The assay was highly specific showing 0.2% cross-reaction with γ-MSH, CLIP, ACTH 11–24 , ACTH 1–14 and ACTH 1–19 .…”
Section: Methodsmentioning
confidence: 99%
“…The interassay variation was 10% and intra-assay variation 5.5%, respectively. Concentrations of ACTH were measured in 50 µl of unextracted plasma as described earlier [33]. The assay was highly specific showing 0.2% cross-reaction with γ-MSH, CLIP, ACTH 11–24 , ACTH 1–14 and ACTH 1–19 .…”
Section: Methodsmentioning
confidence: 99%
“…ACTH in plasma and pituitary extracts was analyzed by a radioimmunoassay described previously [17]. The specific antibody was kindly donated by G.B.…”
Section: Methodsmentioning
confidence: 99%
“…In another report it was suggested that during IIH the main factors triggering ACTH release were of central rather than peripheral origin, and that circulating catecholamines had no direct action at the pituitary level (3). Indeed, the participation of the hypothalamus in the stimulation of ACTH release during hypoglycemia was substantiated by Plotsky et al (4), who reported that IIH in rats resulted in no change in hypophysial portal venous corticotropin-releasing factor (CRF) levels, but caused significant increases in arginine vasopressin (AVP) levels.…”
Section: Introductionmentioning
confidence: 99%